Cross-cultural measurement invariance of the BFI-15p in university students from Argentina, Spain, and Peru - César Merino-Soto; Sergio Dominguez-Lara; Lucas Marcelo Rodriguez; Guillermo M. Chans; Manuel Marti-Vilar (Acta Psychologica)
The Big Five Inventory–15p (BFI-15p) is a relatively new 15-item version developed for Hispanic populations; however, evidence of its cross-cultural equivalence is lacking. This study examined the clarity of item phrasing (Study 1) and measurement invariance (Study 2) in university students from Argentina, Spain, and Peru. Two studies were conducted: one to assess perceived item clarity (n = 70) and another to evaluate the internal structure (n = 737), including dimensionality, reliability, and measurement invariance. In Study 1, consistent item clarity was observed across the three groups, though one item required minor revision. In Study 2, the five-factor structure showed a good fit in the confirmatory factor analysis (CFA), while exploratory structural equation modeling (ESEM) provided slightly better results. However, differences between CFA and ESEM were not substantial, as cross-loadings were close to zero. Omega reliability varied across country groups but was predominantly acceptable for three-item subscales (approximately 0.60). Differential item functioning (DIF) by sex within each country was predominantly negligible. Measurement invariance was supported at the configural, metric, and scalar levels. The findings highlight the implications of measuring the Big Five model in university students across diverse cultural contexts.